2015
DOI: 10.7717/peerj.902
|View full text |Cite
|
Sign up to set email alerts
|

Copepods enhance nutritional status, growth and development in Atlantic cod (Gadus morhuaL.) larvae — can we identify the underlying factors?

Abstract: The current commercial production protocols for Atlantic cod depend on enriched rotifers and Artemia during first-feeding, but development and growth remain inferior to fish fed natural zooplankton. Two experiments were conducted in order to identify the underlying factors for this phenomenon. In the first experiment (Exp-1), groups of cod larvae were fed either (a) natural zooplankton, mainly copepods, increasing the size of prey as the larvae grew or (b) enriched rotifers followed by Artemia (the intensive g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
128
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(144 citation statements)
references
References 67 publications
11
128
1
4
Order By: Relevance
“…Generally, it is unknown which components of zooplankton have positive impacts on fish nutrition. Feeding studies conducted on cod larvae with copepod nauplii in comparison to rotifers revealed that copepod fed fish performed better (Karlsen, van der Meeren, & Rønnestad, 2015). Biochemical analyses of the feed showed that from all analyzed compounds protein, taurine, astaxanthin and zinc were higher on a dry weight basis in copepods than in rotifers and might be components responsible for better performance (Karlsen, van der Meeren, & Rønnestad, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, it is unknown which components of zooplankton have positive impacts on fish nutrition. Feeding studies conducted on cod larvae with copepod nauplii in comparison to rotifers revealed that copepod fed fish performed better (Karlsen, van der Meeren, & Rønnestad, 2015). Biochemical analyses of the feed showed that from all analyzed compounds protein, taurine, astaxanthin and zinc were higher on a dry weight basis in copepods than in rotifers and might be components responsible for better performance (Karlsen, van der Meeren, & Rønnestad, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Feeding studies conducted on cod larvae with copepod nauplii in comparison to rotifers revealed that copepod fed fish performed better (Karlsen, van der Meeren, & Rønnestad, 2015). Biochemical analyses of the feed showed that from all analyzed compounds protein, taurine, astaxanthin and zinc were higher on a dry weight basis in copepods than in rotifers and might be components responsible for better performance (Karlsen, van der Meeren, & Rønnestad, 2015). Also chitin, a main component of cladocerans and copepods, might play a role either as nutrient or as dietary fibre (Gutowska, Drazen, & Robison, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth and development of marine fish larvae is superior when fed zooplankton consisting of their natural diet of copepods rather than the rotifers fed in commercial hatcheries [1][2][3][4]. This difference appears to be linked to differences in nutritional composition between the two zooplankton types, with rotifers having low levels of several nutrients, such as zinc, taurine and/or protein, compared to copepods [3,[5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 96%
“…This difference appears to be linked to differences in nutritional composition between the two zooplankton types, with rotifers having low levels of several nutrients, such as zinc, taurine and/or protein, compared to copepods [3,[5][6][7][8][9]. The lower levels of certain nutrients in rotifers are probably deficient to sustain the high growth rates and successful metamorphosis of larval fish evolutionary adapted to the elevated levels of nutrients typical of copepods in their natural habitat [10,11].…”
Section: Introductionmentioning
confidence: 99%